2019
DOI: 10.1158/1078-0432.ccr-18-3033
|View full text |Cite
|
Sign up to set email alerts
|

PAK Kinase Inhibition Has Therapeutic Activity in Novel Preclinical Models of Adult T-Cell Leukemia/Lymphoma

Abstract: Purpose: To evaluate therapeutic activity of PAK inhibition in ATLL and to characterize the role of PAK isoforms in cell proliferation, survival, and adhesion of ATLL cells in preclinical models. Experimental Design: Frequency and prognostic impact of PAK2 amplification were evaluated in an ATLL cohort of 370 cases. Novel long-term cultures and in vivo xenograft models were developed using primary ATLL cells from North American patients. Two PAK inhibitors were used to block PAK kinase activity pharmacological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…In the study presented herein, we demonstrate the gene and protein level expression patterns of MEF-2 isoforms in multiple ATLL cell lines, and in a specific ATLL cohort termed North American (NA)-ATLL, which exhibit acute clinical manifestations with higher rates of aggressive subtypes compared to chronic counterparts (22). NA-ATLL patients demonstrate chemoresistance and a distinct pattern of somatic mutations (23). Most patients in this cohort showed drastically higher expression of MEF-2A; and also, of MEF-2C in a subset of patients.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In the study presented herein, we demonstrate the gene and protein level expression patterns of MEF-2 isoforms in multiple ATLL cell lines, and in a specific ATLL cohort termed North American (NA)-ATLL, which exhibit acute clinical manifestations with higher rates of aggressive subtypes compared to chronic counterparts (22). NA-ATLL patients demonstrate chemoresistance and a distinct pattern of somatic mutations (23). Most patients in this cohort showed drastically higher expression of MEF-2A; and also, of MEF-2C in a subset of patients.…”
Section: Introductionmentioning
confidence: 84%
“…Since there was elevated MEF-2A and MEF-2C expression in viral-producing and ATLL cell lines, we wanted to assess MEF-2 isoform expression patterns in patient samples to ensure clinical relevance. We characterized a specific HTLV-1-infected NA-ATLL patient cohort (22,23,36) for expression of MEF-2 isoforms and observed a significant logarithmic increase in the expression of MEF-2A in ATLL patients compared to seronegative, asymptomatic carriers and also HAM/TSP patients. We observed a similar trend with MEF-2C expression in a subset of ATLL patients, although they were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our data indicated that the SRC family tyrosine kinases (LCK, LYN) and PAK family kinase (PAK2, PAK3) were the probable targets of the differentially expressed CXC chemokines. These kinases are involved in tumor development and progression by regulating tumor cell proliferation, migration, invasion, and apoptosis [49][50][51]. In CC, differentially expressed CXC chemokines may affect tumor development and progression by regulating these kinases.…”
Section: Discussionmentioning
confidence: 99%